Dielectric characterization of thin films using microstrip ring resonators. Issue 10 (October 2015) - Eng, David L. K.; Olbricht, Benjamin C.; Shi, Shouyuan; Prather, Dennis W.
ABSTRACT This article presents a microstrip ring resonator technique for characterizing thin film substrates up to 110 GHz. A coupling structure was designed to efficiently couple energy into rings despite the tight microstrip‐substrate confinement. Various ring sizes are designed and fabricated, and both dielectric constant and loss tangent results are presented. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:2306–2310, 2015